Implikasi Podcast di Era New Media - Rifqi Fauzi; Irfan Ahmad Harfan (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2020)
The emergence of podcasts in the digital era has become a new alternative for audiences who are getting bored with existing audio content. In today's digital era, technology is being consumed massively, podcasts play a role in shaping people's thinking, behavior and culture. This study aims to determine the implications of podcasts in changing audience thinking and behavior. This study uses a qualitative method with a case study approach. The data collection techniques used were through observation, in-depth interviews, and documentation study. The data analysis technique used in this study is a qualitative descriptive analysis technique. Meanwhile, the data validity test was checked using the source triangulation technique. The results of the research show that the existence of Podcasts in the digital era cannot be separated from its very flexible accessibility. Podcasts are the only media that includes a variety of interesting information content that can be consumed or enjoyed through applications connected via the internet network. In addition, listening to podcasts can have a very influential impact on the audience, from cognitive, behavioral, to cultural aspects in society.